Humoral responses to herpesviruses are associated with neurodegeneration after a demyelinating event: results from the multi-center set study - Zivadinov, Robert; Chin, Jamie; Horakova, Dana; Bergsland, Niels; Weinstock-Guttman, Bianca; Tamaño-Blanco, Miriam; Badgett, Darlene; Hagemeier, Jesper; Tyblova, Michaela; Carl, Ellen; Krasensky, Jan; Vaneckova, Manuela; et al. (Journal of neuroimmunology, 2014)
OBJECTIVES: To investigate the associations between antibody responses to herpesviruses and the development of thalamic, total deep gray matter, cortical and central atrophy in high-risk clinically isolated syndromes (CIS) after the first demyelinating event. METHODS: We analyzed volumetric brain outcomes in 193 CIS patients enrolled in a multi-center study of high-risk CIS. All patients had 2 or more MRI brain lesions and two or more oligoclonal bands in cerebrospinal fluid. Serum samples obtained at the screening visit prior to any treatment were analyzed for IgG antibodies against cytomegalovirus (anti-CMV) and Epstein-Barr virus (EBV) viral capsid antigen (VCA). All patients were treated with interferon-beta. Clinical and MRI assessments were obtained at baseline, 6, 12, and 24 months. RESULTS: Anti-EBV VCA highest quartile status was associated with regional atrophy measures for percent decrease in thalamus. Anti-CMV positivity was associated with greater total deep gray matter atrophy and whole brain atrophy. Anti-EBV VCA highest quartile status was associated as trends with greater whole brain, gray matter atrophy and central atrophy. The associations of anti-EBV VCA antibodies with thalamic atrophy were mediated by its associations with T2 lesions whereas the associations of anti-CMV positivity with deep gray matter atrophy were relatively independent of T2 lesions. CONCLUSIONS: Antibody responses to EBV and CMV are associated with global and regional brain atrophy in CIS patients treated with interferon-beta.
Keywords: antigeny virové; Leukoencephalopathies; Cytomegalovirus; Magnetic Resonance Imaging; Interferon-beta; časové faktory; demyelinizační nemoci; Adult; Male; Deep gray matter atrophy; lidé; Atrophy; longitudinální studie; Humans; Neurodegenerative Diseases; thalamus; pozorování; Epstein–Barr virus; Young Adult; virové plášťové proteiny; Capsid Proteins; Observation; protilátky virové; Time Factors; Antiviral Agents; antivirové látky; Thalamus; mužské pohlaví; Antigens, Viral; Herpesviridae; interferon beta; Antibodies, Viral; dospělí; atrofie; mladý dospělý; Demyelinating Diseases; ženské pohlaví; Female; leukoencefalopatie; magnetická rezonanční tomografie; Environmental factors; Longitudinal Studies; neurodegenerativní nemoci